2021
DOI: 10.3168/jds.2021-20483
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal level of dietary cation-anion difference fed to prepartum nulliparous cows on offspring acid-base balance, metabolism, and growth

Abstract: The objectives were to determine the effects of dietary cation-anion difference (DCAD) fed to pregnant cows during the last 22 d of gestation on offspring acid-base balance, metabolism, growth, and health preweaning. A total of 132 nulliparous Holstein cows were enrolled at 250 (248 to 253) d of gestation in a randomized block design. Cows were blocked by genomic merit of energy-corrected milk yield and assigned randomly to diets varying in DCAD: +200 (P200, n = 43), −50 (N50, n = 45), or −150 (N150, n = 44) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
2
1
Order By: Relevance
“…Preweaning growth of beef and beef cross calves born to Holstein dams (H ET and A × H) was similar to the results of Orellana Rivas et al (2022) who found ADG of 0.60 to 0.65 kg/d until 63 d among Holstein calves feed 0.65 to 0.76 kg of milk dry matter per day. However, growth performance was lesser than that reported by Zimpel et al (2021) who found ADG of 0.77 to 0.81 kg/d until d 56 among Holstein calves and Welk et al (2022) who found ADG of 0.70 to 0.88 kg/d until 70 d. The calves feed by Zimpel et al consumed ~0.35 kg more milk dry matter per day than was offered to the calves in the present study, and the calves fed by Welk et al were offered twice the volume of milk offered to the calves in the present study. Growth of the calves in the present study was likely limited by quantity of milk dry matter offered in the first 2 mo of life.…”
Section: Discussioncontrasting
confidence: 70%
“…Preweaning growth of beef and beef cross calves born to Holstein dams (H ET and A × H) was similar to the results of Orellana Rivas et al (2022) who found ADG of 0.60 to 0.65 kg/d until 63 d among Holstein calves feed 0.65 to 0.76 kg of milk dry matter per day. However, growth performance was lesser than that reported by Zimpel et al (2021) who found ADG of 0.77 to 0.81 kg/d until d 56 among Holstein calves and Welk et al (2022) who found ADG of 0.70 to 0.88 kg/d until 70 d. The calves feed by Zimpel et al consumed ~0.35 kg more milk dry matter per day than was offered to the calves in the present study, and the calves fed by Welk et al were offered twice the volume of milk offered to the calves in the present study. Growth of the calves in the present study was likely limited by quantity of milk dry matter offered in the first 2 mo of life.…”
Section: Discussioncontrasting
confidence: 70%
“…There are conflicting results on the effects of feeding anionic diets to dairy cows precalving on calf acidosis, colostrum Ig absorption, and serum Ig concentration ( Quigley and Drewry, 1998 ). The most recent study by Zimpel et al (2021) found no effect of maternal DCAD on colostral Ig content or apparent efficiency of absorption of Ig or performance of dairy calves.…”
mentioning
confidence: 90%
“…Studies in dairy cows have shown that peripartum maternal hypocalcemia is associated with increased incidence of neonate enteritis ( Hunter, 2015 ) and respiratory disease ( Wilhelm et al, 2017 ) and that feeding a low DCAD diet to dairy cows can result in increased incidence of diarrhea and treatments in their calves ( Rajaeerad et al, 2020 ). However, results may depend on the degree and duration of the DCAD as no effect on Ig absorption, calf morbidity, or performance was found in some recent dairy cow studies ( Collazos et al, 2017 ; Zimpel et al, 2021 ).…”
mentioning
confidence: 96%